Rates and methods of phosphorus application in cabbage crop - Duarte, Luiz Otavio [UNESP] (2019)
The efficiency of phosphate fertilization may be reduced by incorporating the fertilizer to the soil using a rotary tiller, which is a method commonly adopted to grow vegetables. This study aimed to evaluate the yield of cabbage crop and the efficiency of phosphate fertilization based on rates and application methods of P to the soil. Four experiments were carried out [two using broadcasting application (0 kg ha(-1) 200 kg ha(-1), 400 kg ha(-1), 800 kg ha(-1) and 1,600 kg ha(-1) of P2O5 ) and two using localized application (0 kg ha(-1), 80 kg ha(-1), 160 kg ha(-1), 320 kg ha(-1) and 640 kg ha(-1) of P2O5, combined with the presence or absence of phosphating - application of 200 kg he of P2O5 by broadcasting)] in two growing sites [one with low (A) and another with high (B) content of P, both showing a very clayey texture]. The rates of 252 kg ha(-1 )and 284 kg ha(-1) of P2O5 were estimated to obtain the maximum economic productivity in the broadcasting application at the sites A and B, respectively. The best rates were 183 kg ha(-1) and 146 kg ha(-1) of P2O5 with the localized application of P without phosphating at the sites A and B, respectively. To obain 95 % of maximum yield, the recovery efficiency was 48.9 % and 30.0 % at the sites A and B, respectively. For the localized application of P in the absence of phosphating, these values were 44.6 %and 60.4 % at the sites A and B, respectively. With phosphating, the recovery efficiency decreased significantly. The localized application of P is more efficient than the broadcasting application to supply nutrients and increase the cabbage yield.